1989
DOI: 10.1007/bf01014700
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variation in defense secretions of malaysian termites from the genusNasutitermes (Isoptera, nasutitermitinae)

Abstract: The defense secretions of five species of MalaysianNasutitermes,N. longinasus, N. matangensis, N, havilandi, N. johoricus, andNasutitermes species 01, are compared.N. longinasus andN. species 01 provide trinervitene alcohols,N. havilandi mainly tricyclic trinervitene and tetracyclic kempane alcohols and acetates, whereasN. matangensis furnish acetyl/propionyl derivatives of trinervita-11(12),15(17)-dien-3α,9β,13α-triol (XXI and XXII). A new diterpene, assigned as trinervita-11(12),15(17)-dien-3α,13α-diol-3,13-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…novarumhebridarum has clear affinities with N. matangensis, which were previously pointed out (Roisin and Pasteels, 1996: p. 543): in addition to being hardly distinguishable by morphological characters, both are arboreal nesters which produce a defensive secretion characterized by the same major propionate diterpene derivatives and monoterpenes (Dupont et al, 1981;Chuah et al, 1989). Like N. matangensis and N. takasagoensis, N. novarumhebridarum is able to produce ergatoid replacement reproductives (Roisin and Pasteels, 1987).…”
Section: New Guinean Speciesmentioning
confidence: 86%
“…novarumhebridarum has clear affinities with N. matangensis, which were previously pointed out (Roisin and Pasteels, 1996: p. 543): in addition to being hardly distinguishable by morphological characters, both are arboreal nesters which produce a defensive secretion characterized by the same major propionate diterpene derivatives and monoterpenes (Dupont et al, 1981;Chuah et al, 1989). Like N. matangensis and N. takasagoensis, N. novarumhebridarum is able to produce ergatoid replacement reproductives (Roisin and Pasteels, 1987).…”
Section: New Guinean Speciesmentioning
confidence: 86%
“…4), suggesting that Ntsp1 protein is constantly synthesized after differentiation to soldier, and secreted and stored in the reservoir. Although terpenoids isolated from frontal gland secretions of Nasutitermes have been analyzed chemically (Prestwich, 1979c;Goh et al, 1982;Gush et al, 1985;Everaerts et al, 1988Everaerts et al, , 1993Chuah et al, 1989), no protein has been so far identified in the secretion.…”
Section: Article In Pressmentioning
confidence: 99%
“…A large part of the soldier's head is occupied by the frontal gland reservoir, in which large amount of secretions are stored (Costa-Leonardo and De Salvo, 1987). The components of the frontal gland secretions of Nasutitermes include various types of terpenoids (Prestwich, 1979c;Goh et al, 1982;Gush et al, 1985;Everaerts et al, 1988Everaerts et al, , 1993Chuah et al, 1989). Although detailed biosynthetic pathways of the secretions have not been investigated in any termite species, it was suggested that the soldiers synthesize these secretions by themselves in Nasutitermes (Prestwich et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…1). These soldiers can discharge defensive secretions (diterpene) from the frontal pore by the contraction of muscles around the frontal gland reservoir (Chuah et al 1989;Noirot 1969). These soldiers can discharge defensive secretions (diterpene) from the frontal pore by the contraction of muscles around the frontal gland reservoir (Chuah et al 1989;Noirot 1969).…”
Section: Introductionmentioning
confidence: 99%